Left in the West : Literature, Culture, and Progressive Politics in the American West - Woods, Gioia, 1968- (Book collections on Project MUSE., 2018)
"Left in the West is an edited collection bringing together histories, biographies, close readings, and theories about the literary and cultural left in the American West, especially as it is distinct from the more often-theorized literary left in New York and major eastern metropolitan centers. The collection argues for a new understanding of the relationship between region, progressive political engagement, and literary and cultural work; Woods and her contributors examine the West as a unique socio-political region shaped by specific environmental, social, economic, and ethnic concerns. While the literary left in the West shared many interests with other regional expressions of "left," including labor, class, anti-fascism, and anti-imperialism, the influence of Manifest Destiny and the distinct history of settler colonialism in western territories caused western leftists to develop concerns unique to the region, elevating issues of industrialization and environmental degradation, Native American sovereignty, and immigrant communities' access to power. And as this collection of essays makes clear, western leftists were (and are) deploying a broad range of literary genres and cultural techniques to address these unique concerns"--Provided by publisher.